Sulfur‐bearing phases detected by evolved gas analysis of the Rocknest aeolian deposit, Gale Crater, Mars. Issue 2 (15th February 2014) - McAdam, Amy C.; Franz, Heather B.; Sutter, Brad; Archer, Paul D.; Freissinet, Caroline; Eigenbrode, Jennifer L.; Ming, Douglas W.; Atreya, Sushil K.; Bish, David L.; Blake, David F.; Bower, Hannah E.; Brunner, Anna; et al.
Abstract The Sample Analysis at Mars (SAM) instrument suite detected SO2, H2S, OCS, and CS2 from ~450 to 800°C during evolved gas analysis (EGA) of materials from the Rocknest aeolian deposit in Gale Crater, Mars. This was the first detection of evolved sulfur species from a Martian surface sample during in situ EGA. SO2 (~3–22 µmol) is consistent with the thermal decomposition of Fe sulfates or Ca sulfites, or evolution/desorption from sulfur‐bearing amorphous phases. Reactions between reduced sulfur phases such as sulfides and evolved O2 or H2O in the SAM oven are another candidate SO2 source. H2S (~41–109 nmol) is consistent with interactions of H2O, H2 and/or HCl with reduced sulfur phases and/or SO2 in the SAM oven. OCS (~1–5 nmol) and CS2 (~0.2–1 nmol) are likely derived from reactions between carbon‐bearing compounds and reduced sulfur. Sulfates and sulfites indicate some aqueous interactions, although not necessarily at the Rocknest site; Fe sulfates imply interaction with acid solutions whereas Ca sulfites can form from acidic to near‐neutral solutions. Sulfides in the Rocknest materials suggest input from materials originally deposited in a reducing environment or from detrital sulfides from an igneous source. The presence of sulfides also suggests that the materials have not been extensively altered by oxidative aqueous weathering. The possibility of both reduced and oxidized sulfur compounds in the deposit indicates a nonequilibrium assemblage. Understanding the sulfur mineralogy in Rocknest materials, which exhibit chemical similarities to basaltic fines analyzed elsewhere on Mars, can provide insight in to the origin and alteration history of Martian surface materials.